Physiological and biochemical responses of hybrid maize (Zea mays L.) varieties grown under heat stress conditions - Tas, Timucin (PeerJ, 2022)
Maize (Zea mays L.) is the second most commonly produced and consumed crop after wheat globally and is adversely affected by high heat, which is a significant abiotic stress factor. This study was carried out to determine the physiological and biochemical responses of hybrid corn varieties under heat stress (‘HS’) compared to control (‘C’) conditions during the 2020 and 2021 growing seasons. The experiment was conducted under natural conditions in the Southeastern region of Turkey, where the most intense temperatures are experienced. This experiment used split plots in randomized blocks with three replications, with ‘HS’ and ‘C’ growing conditions applied to the main plots and the different hybrid corn varieties (FAO 650) planted on the sub plots. Mean values of days to 50% tasseling (DT, day), grain yield (GY, kg ha−1), leaf water potential (LWP, %), chlorophyll-a (Chl-a, mg g−1), cell membrane damage (CMD, %), and total phenol content (TPC, μg g−1) were significantly different between years, growing conditions, and hybrid corn varieties. Changes in the climate played a significant role in the differences between the years and growing conditions (GC), while the genetic characteristics of the different corn varieties explained the differences in outcomes between them. The values of DT, GY, LWP, Chl-a, CMD, and TPC ranged from 49.06–53.15 days, 9,173.0–10,807.2 kg ha−1, 78.62–83.57%, 6.47–8.62 mg g−1, 9.61–13.54%, and 232.36–247.01 μg g−1, respectively. Significant correlations were recorded between all the parameters. Positive correlations were observed between all the variables except for CMD. The increased damage to cell membranes under ‘HS’ caused a decrease in the other measured variables, especially GY. In contrast, the GY increased with decreased CMD. CMD was important in determining the stress and tolerance level of corn varieties under ‘HS’ conditions. The GY and other physiological parameters of ADA 17.4 and SYM-307 candidate corn varieties surpassed the control hybrid corn cultivars. The results revealed that the ADA 17.4 and SYM-307 cultivars might have ‘HS’-tolerate genes.
Keywords: Maize; Heat stress; Cell membrane damage; Chlorophyll